Proceedings of the Third Annual Workshop on Lifelog Search Challenge 2020
DOI: 10.1145/3379172.3391724
|View full text |Cite
|
Sign up to set email alerts
|

LifeSeeker 2.0: Interactive Lifelog Search Engine at LSC 2020

Abstract: In this paper we present our interactive lifelog retrieval engine in the LSC'20 comparative benchmarking challenge. The LifeSeeker 2.0 interactive lifelog retrieval engine is developed by both Dublin City University and Ho Chi Minh University of Science, which represents an enhanced version of the two corresponding interactive lifelog retrieval engines in LSC'19. The implementation of LifeSeeker 2.0 has been designed to focus on the searching by text query using a Bag-of-Words model with visual concept augment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…The system was evaluated by four users and findings indicate that the system can be effectively used to locate relevant content. User studies showed that the users generally liked the system, but both observation and feedback provided a list of proposed enhancements to the system, which have been integrated into a new interactive retrieval system called LifeSeeker [9] which was shown to be among the best performers at the LSC2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was evaluated by four users and findings indicate that the system can be effectively used to locate relevant content. User studies showed that the users generally liked the system, but both observation and feedback provided a list of proposed enhancements to the system, which have been integrated into a new interactive retrieval system called LifeSeeker [9] which was shown to be among the best performers at the LSC2019.…”
Section: Discussionmentioning
confidence: 99%
“…Through feedback and observation of the users using the retrieval system, we gathered findings that are being used to improve the current system for the LSC'19 (Lifelog Search Challenge) comparative benchmarking exercise. The new system called LifeSeeker [9] is an evolution of this system that incorporated the following updates:…”
Section: User Feedbackmentioning
confidence: 99%
“…With different considerations, Myscéal [28] viewed this as a document retrieval problem by indexing textual annotations and matching with textual queries. Embedding techniques are also commonly based on the idea of encoding concepts from both queries and images tags into the same vector space to calculate the similarity between them [19,20]. Regarding using graphs, LifeGraph [25] applied knowledge graph structure with the nodes representing detected things or scenes recognized in images.…”
Section: Related Workmentioning
confidence: 99%
“…Che et al [2] integrate relationship-mapping between objects and subjects in the lifelog images. LifeSeeker 2.0 is an enhancement to the 2019 tool of the same name [12], supporting interactive graph-based filtering. The FIRST system [20] is designed to be a flexible integration platform for easy use of new query workflows and visualization layouts.…”
Section: Participating Systemsmentioning
confidence: 99%